Patrick Blackett : sailor, scientist, and socialist - Hore, Peter (F. Cass, 2003)
This edited volume comprises a series of essays about Patrick Maynard Stewart Blackett, one of the greatest scientists of the 20th century, as well as a prominent figure in the Royal Navy and British politics.